Retrospective and contemporary predictors of National Collegiate Athletic Association Division I cross-country performance are sex specific - Carder, M. J.; Scudamore, E. M.; Savanna, K. N.; Pribyslavska, V.; Bowling, L. R.; O'Neal, E. K. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to identify National Collegiate Athletic Association (NCAA) Division I cross-country (XC) performance potential using laboratory-based and field-based parameters and retrospective high school (HS) personal best (PB) data at various distances of current collegiate XC runners. Fifteen female and 17 male NCAA XC runners provided their PB for 5-km (women) and 8-km (men) distances from the previous season. Bivariate correlation and stepwise and hierarchical regression modeling were used to predict XC performance. Single squat jump height and multijump reactive strength index displayed r < 0.27 for both sexes, suggesting lower-body power is a poor predictor of XC performance or masked by other factors of greater importance. Triceps skinfold thickness approached significance (r = 0.43; p = 0.09) for men but was unrelated to women's performance (r = -0.05; p = 0.86). HS XC PB neared significance (r = 0.55, p = 0.054), but no other single or combination of variables reached significance for female runners. Aerobic capacity displayed a moderate to strong relationship (r = 0.65) for male runners. High school 3,200-m PB for men produced a robust prediction capacity (r = 0.85; p = 0.005, SEE = ± 0.65 minutes), and predicted 8-km PB within 30 seconds for approximately two-thirds of runners. These outcomes suggest when recruiting HS or transfer athletes, male and female XC runners should not be recruited on the same factors. Women's XC PB is more difficult to predict, but skinfold thickness was statistically the least valuable predictor of all factors.